Authors and audiences : popular Canadian fiction in the early twentieth century - Karr, Clarence, 1941- (McGill-Queen's University Press, 2000)
"From the 1890s through the 1920s, the best-selling fiction of Ralph Connor, Robert Stead, Nellie McClung, Lucy Maud Montgomery, and Arthur Stringer was internationally recognized. In this intriguing cultural history of the conception, production, and reception of popular fiction, Clarence Karr challenges the common assumption that best-sellers are a conservative cultural influence, reflecting and promoting traditional values. By focusing on a society and its cultural leaders at a period when they were coming to grips with modernity, Karr provides a new perspective on culture and the interaction between readers and popular authors." "Authors and Audiences reveals the cultural milieu that gave rise to the golden age of hardcover fiction. Karr describes the relationships between authors, literary agents, and publishers in Toronto, London, New York, and other centers; examines the relationship between authors and the movie industry; and discusses the reception of fiction by critics and readers. This is the first Canadian study to use fan mail to highlight readers' interactions with author and text. Karr places the authors' careers in an international setting and shows how, despite living a considerable distance from the leading cultural production centers of New York and London, they became internationally recognized and read."--Jacket